Islamic Bank Efficiency and Productivity in Malaysia - Torabi, Rezvan (2011)
The present empirical study investigates the efficiency of full-fledged Islamic banks and Islamic window operations of domestic and foreign banks in Malaysia. This study measures the technical, Allocative, pure technical, scale and cost efficiency of these banks using the Data Envelopment Analysis (DEA) technique for the period 1997-2008. During this period, Islamic banking system in Malaysia has two phases of development. This is a pioneer study that analyzes the polices of central bank of Malaysia in both phases and compares the efficiency of Islamic banking industry in these phases. In general, the results show that on average, the efficiency of the Islamic banking industry increases in these phases which corresponds positively to their deposits, asset and financing growth. This could suggest that the entrance of the second full fledge Islamic bank in the second phase and the entrance of foreign full fledge banks in the third phase had given a positive impact on the efficiency of Islamic banking industry as a whole. The findings also indicate that the full fledge Islamic banks are more efficient than Islamic windows. In the comparison of efficiency levels with respect to ownership, the foreign bank is found to be more efficient than domestic banks in full fledge banking system, however in Islamic windows, the domestic banks are found to be more efficient than foreign banks. This study also investigates the productivity of full-fledged Islamic banks and Islamic window operations of domestic and foreign banks in Malaysia. It measures the efficiency change, technological change and total factor productivity of these banks using the Malmquist Index for the period 1997-2008. This is a pioneer study that has analyzes polices of central bank of Malaysia in both phases and has compared the productivity of Islamic banking industry in these phases. In general, the results show that on average, the productivity of the Islamic banking industry has increased in these phases which correspond positively to their deposits, assets and financing growth. This could suggest that the entrance of the second full fledge Islamic bank in second phase and the entrance of foreign full fledge banks in third phase made a positive impact on the productivity of Islamic banking industry as a whole. The findings also indicate that the mean TFP for full fledge Islamic banks is larger than the same figure for Islamic windows. The comparison of productivity levels with respect to ownership, in both systems (full fledge and Islamic windows) shows that the mean TFP for domestic banks is greater than the figure for foreign banks. The sources of productivity growth in the Islamic banking industry as a whole show a gradual improvement in efficiency change. However, the increase in efficiency progress in the Islamic banking industry was marginally offset by the declined in technological change, which led to lower productivity growth. The study about measurement of efficiency that describes and analyzes the determining factors of efficiency is useful. The recognition and utilization of the key factors which have significant influence on the efficiency of the firm are important. So, in this study a range of bank specific factors and regularity factors which may influence Islamic bank efficiency is considered. This study used three different methods to determine the impact of these factors on Islamic banks’ efficiency, namely, OLS, Tobit and Bootstrap methods. However, there is not any difference in the results derived from these three methods. The findings suggest that, bank size; capital adequacy and loan activity are positively related to the efficiency of Islamic banks. The findings also confirm that the proxy of Credit risk as measured by the ratio of loan loss provision to total loan has negative effects on the Islamic banking efficiency.